Dynamic Modulus Characteristics of Bound Cement-Treated Crushed Rock Base course - Nusit, K.; Jitsangiam, Peerapong; Nikraz, Hamid; Hewa Thalagahage, R. (Suranaree University of Technology, 2014)
Cement-treated base is a conveniently and effectively stabilised pavement material consisting of a mixture of standard base course materials blended with a prescribed amount of Portland cement and water. The cement-treated base material is suitable for use in high-traffic roads and airfield pavements, and usually provides superior engineering properties compared to standard road base material. However, fully bound or stabilised cement-treated base is a relatively stiff pavement base material which is prone to fatigue failure under repeated loading. In pavement design, current fatigue models for cement-treated base material remain empirical, and there exists a lack in scientific linkage between the models themselves and real fatigue perfor-mance. Consequently, a more reliable fatigue deterioration model for cement-treated base is required in order to maximise the usage of such material in pavements. The provision of ‘bottom-up’ constitutive equations is preferable when seeking a deeper understanding of cement-treated base course behaviour under repeated loading. This study focuses on evaluating the dynamic moduli (i.e., the moduli under cyclic loading conditions), of cement-treated base under traffic loads. The same testing basis used for asphalt concrete was adopted in this research. As such, the dynamic moduli were measured under different temperatures and loading frequencies, based on the dynamic modulus testing protocol for asphalt concrete. Test results revealed that cement content and curing time significantly influence the dynamic modulus of bound cement-treated base course. However, the dynamic modulus property was slightly affected by the changes in temperature and loading frequency within a specific range of testing conditions of the test protocol. At the end of this research, a predictive equation for the dynamic modulus was tentatively put forward. This equation was developed from the relationship of the modulus to the unconfined compressive strength. It should be noted that this predictive equation requires further verification due to its development being based on limited number of test samples and results.Cement-treated base is a conveniently and effectively stabilised pavement material consisting of a mixture of standard base course materials blended with a prescribed amount of Portland cement and water. The cement-treated base material is suitable for use in high-traffic roads and airfield pavements, and usually provides superior engineering properties compared to standard road base material. However, fully bound or stabilised cement-treated base is a relatively stiff pavement base material which is prone to fatigue failure under repeated loading. In pavement design, current fatigue models for cement-treated base material remain empirical, and there exists a lack in scientific linkage between the models themselves and real fatigue performance. Consequently, a more reliable fatigue deterioration model for cement-treated base is required in order to maximise the usage of such material in pavements. The provision of ‘bottom-up’ constitutive equations is preferable when seeking a deeper understanding of cement-treated base course behaviour under repeated loading. This study focuses on evaluating the dynamic moduli (i.e., the moduli under cyclic loading conditions), of cement-treated base under traffic loads. The same testing basis used for asphalt concrete was adopted in this research. As such, the dynamic moduli were measured under different temperatures and loading frequencies, based on the dynamic modulus testing protocol for asphalt concrete. Test results revealed that cement content and curing time significantly influence the dynamic modulus of bound cement-treated base course.However, the dynamic modulus property was slightly affected by the changes in temperature and loading frequency within a specific range of testing conditions of the test protocol. At the end of this research, a predictive equation for the dynamic modulus was tentatively put forward. This equation was developed from the relationship of the modulus to the unconfined compressive strength. It should be noted that this predictive equation requires further verification due to its development being based on limited number of test samples and results.